The Influence Of Business Strategy And Earnings Management On The Potential Bankruptcy With Profitability As A Moderating Variable - Fadhillah Akbar Rachman; Atik Djayanti (Jurnal Mantik, 2022)
This research was carried out with the aim of knowing how much influence business strategy (cost leadership strategy and differentiation strategy) and earnings management have on potential bankruptcy with profitability as a moderating variable in consumer goods industry sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016 - 2020 period. With purposive sampling technique, the sample companies in this study were 15 companies. This study uses multiple regression models and types of secondary data from 2016 to 2020. This study tested the hypothesis with a regression model. The results of the study conclude that the cost leadership business strategy has a negative influence on the potential for bankruptcy, the differentiation business strategy has a negative influence on the potential for bankruptcy, and earnings management has a positive influence on the potential for bankruptcy. While profitability is able to moderate the effect of cost leadership strategy and differentiation strategy on bankruptcy potential, it is unable to moderate the effect of earnings management on bankruptcy potential.